2024
DOI: 10.1109/access.2024.3351811
|View full text |Cite
|
Sign up to set email alerts
|

Zero Voltage Switching for High Power Three-Phase Inductive Power Transfer With a Dual Active Bridge

Chao Cui,
Daniel Pehrman,
Yujing Liu
et al.

Abstract: Inductive power transfer (IPT) technology used for charging electric vehicles faces challenges in transferring high power because the power capacity and switching losses of high-frequency semiconductor devices are limiting factors. A three-phase system is a common high-power solution and soft switching is crucial for efficiency-oriented applications with high switching frequencies. In addition, dual active bridge (DAB) topology is a suitable topology for soft switching and has advantages in controllability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…By comparing the conditions of realizing CC mode and ZPA conditions (12), it can be found that under the above conditions (21), either of the two cascaded T-circuits can also achieve CC mode and ZPA conditions.…”
Section: Constant Output Voltage Mode Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the conditions of realizing CC mode and ZPA conditions (12), it can be found that under the above conditions (21), either of the two cascaded T-circuits can also achieve CC mode and ZPA conditions.…”
Section: Constant Output Voltage Mode Analysismentioning
confidence: 99%
“…Thus, the dc-dc converter is the key to the battery chargers. Among the many topologies of the dc-dc converters, the LLC topology is a popular candidate for dc-dc converter by means of the inherent advantages, such as zero-voltage-switching (ZVS) for MOSFETs of the inverter, zero-current-switching (ZCS) for diodes of the rectifier and simple structure [11][12][13]. However, for common LLC converters which usually adopt pulse frequency modulation (PFM) control, wide load variation in battery charging can result in a wide output voltage range, which requires a corresponding wide variation range of switching frequency accordingly [14].…”
Section: Introductionmentioning
confidence: 99%